CHARGING DIRECTOR OF COMPANY WITH PERSONAL BANKRUPTCY FOR COMPANY MISMANAGEMENT - M. Hadi Shubhan (Jurnal Hukum dan Peradilan, 2019)
This study aims to examine the theories, regulations, and practices at the commercial court in Indonesia regarding the possibility of charging director of limited liability companies (LLC, Perseroan Terbatas(PT)) with personal bankruptcy as a form of personal liability due to mismanagement causing the company to go bankrupt. This is an interesting issue to study because, in general, the rights and obligations of the company, and specifically LLC in this article, are separated from the rights and obligations of the directors. Therefore, the company’s liability cannot be requested upon its directors’ personal liability. Nonetheless, this general principle is revocable if the director makes an error which causes the company to go bankrupt. This study uses the normative (doctrinal) legal research method with statute approach, conceptual approach, and cases approach. The study results revealed that directors could be asked for personal liability if they create problems which lead to a company going bankrupt. The director's liability comes in the form of the obligation to file bankruptcy for the director him/herself. In this study, several cases were found that punished the director with the director's personal bankruptcy, like in the case of  personal bankruptcy of director  PT QSAR and  in the case personal bankruptcy of director of PT CHK.